Ergonomic Analysis to Assess Comfort and Risk of Musculoskeletal Injuries in Office Workers at PT X Using Rosa's Method - Siregar, Baharuddin; Wahyuni, Dewi Sri; Indriani, Fatma; Dalimunthe, Nadiyah Rahma; Zakwan, M. Hadin; Asti, Rahmah Dwi; Darmansyah, Rendi (Yayasan Jompa Research and Development, 2025)
Abstract This study aims to analyze the level of workplace comfort and the risk of musculoskeletal injuries among office workers at PT X using the Rapid Office Strain Assessment (ROSA) and Nordic Body Map (NBM) methods, as well as to examine the relationship between working posture and MSD complaints. This study uses a quantitative descriptive design with a cross-sectional approach involving 50 respondents. The results indicate that most employees are categorized as having a moderate ergonomic risk (ROSA score 4-5), while a small portion has a high ergonomic risk (score 5). Based on the NBM results, most workers experience mild to moderate musculoskeletal complaints, particularly in the neck, shoulders, lower back, and wrists. The main factors contributing to ergonomic risk are non-adjustable office chairs and desks, as well as prolonged static working postures. Overall, the ergonomic conditions at PT X are relatively good. However, improvements in workstation facilities and increasing workers' awareness of ergonomic principles are necessary to reduce the risk of musculoskeletal injuries and enhance workplace comfort. As a large-scale plantation company, PT X faces a high potential risk of Musculoskeletal Disorders (MSDs) among its employees. This risk primarily stems from the nature of the work, which often requires repetitive or static activities.